Pengaruh Perbedaan Ukuran Mata Pancing Terhadap Hasil Tangkapan Nelayan Pancing Ulur Desa Molahu Kecamatan Paguat Kabupaten Pohuwato - Husain, Ratmin; Salam, Aziz; Nursinar, Sitti (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This research aims to determine the highest number of fish catches based on the size of the hook in the operation of hand-line fishing equipment and to determine the effect of differences in the size of the line on the catch of hand-line fishermen in Molamahu Village, Paguat District, Pohuwato Regency. This research was carried out from June 2019 to January 2020. The method used in this research was experimental fishing. Observations were carried out 15 times, each trip was divided into 3 boats, using a Completely Randomized Design (CRD), data analysis using the data normality test (Liliefors test), homogeneity test using the barlet test, hypothesis testing (one way anova) and the BNT follow-up test ( Smallest Real Difference). The results of the research show that all types of fishermen's catches amounted to 9 families of coral fish, where fishing hook No. 17 obtained more catches compared to hook No. 17. 10, no. 14 and No. 20 with the number of fishing hooks caught No. 17 as many as 432 heads. The results of the BNT test analysis show that, the comparison of the number of catches using fishing hook No. 17 and No. 20, no. 17 and 14, No. 17 and No. 10, No. 20 and No. 14, No. 20 and No. 10 are significantly different.